Analysis of Economic Value Added and Market Value Added to Measure Financial Performance in Pulp and Paper Companies - Wahab Edi Saputra; Agus Sukoco; Joko Suyono; Damasari Ratnasahara Elisabeth (IJEBD (International Journal of Entrepreneurship and Business Development), 2019)
Purpose: The purpose of this study was to determine the company's financial performance in the pulp and paper industry which was measured using the concept of Economic Value Added (EVA) and Market Value Added (MVA) during the period 2017 and 2018. Design/methodology/approach: Research data is obtained through related websites and literature review. Findings: The results of the measurement of EVA and MVA for the period 2017 and 2018 show only PT.Alkindo Naratama, Tbk. which adds to the economic value of the company and market value added (> 0). Research limitations/implications: The population in this study consisted of all pulp and paper companies that had go public and be listed on the Indonesia Stock Exchange (IDX), which is as many as nine companies, then do the purposive sampling selection which obtained a sample of four companies. Practical implications: While three companies, namely PT. Kedawung Setia Industrial, Tbk. PT.Suparma, Tbk. and PT. Kertas Basuki Rachmat, Tbk. experience instability in EVA and MVA. Originality/value: